Book review: Whitney Cox, Politics, Kingship, and Poetry in Medieval South India: Moonset on Sunrise Mountain. (April 2019) - Devadevan, Manu V.
Whitney Cox, Politics, Kingship, and Poetry in Medieval South India: Moonset on Sunrise Mountain, New Delhi: Cambridge University Press, 2017, xvi + 312 pp.